Evaluation of the bioluminescence activity, biokinetics, and the effects of binary mixtures of inducers on the Pm-lux recombinant strain - Kong, In Chul; Lee, Sohyeon; Ha, Kyoochul; Ko, Kyung-Seok (Frontiers in Environmental Science, 2022)
The bioluminescence activity and biokinetics of a recombinant Pseudomonas putida mt-2 were investigated in the presence of various inducers: three chlorotoluenes (CTs) and two nitrotoluenes (NTs). The effects of binary mixtures (40 combinations) of eleven inducers on the bioluminescence activity were also studied. Different responses and toxicities were observed depending on the type of inducers and concentrations. The intensity of the bioluminescent response at 1 mM of individual inducers was in the following order: o-CT > p-CT > m-CT > o-NT, and p-NT. The biokinetics calculated based on the bioluminescence activity was in the range of 0.109–8.417 mM for the half-saturation constant (Ks) and 6.083–19.880 h-1 for the maximum SBR (µmax). In the case of binary mixtures, the observed bioluminescence was 4–810% (avg. 80.4 %) of the expected bioluminescence intensity depending on the combinations (0.0001 < p < 0.5226). Among these binary mixture combinations, 27 out of 40 combinations indicated antagonistic effects (3–83% of expected activity; p < 0.0391) under the exposure of inducer mixtures. Overall, this study demonstrated that the proper biomonitoring for specific chemicals could be established by considering the characteristics of mixture pollutants as their possible usages as preliminary rapid and field analytical bio-tool.